Too Risk Averse to Stay Honest? Business Corruption, Uncertainty and Attitudes Toward Risk - Soreide, T. (2012)
The presence of business-corruption provokes firms to make choices between legal business approaches and illegal bribery. The outcome of a chosen strategy will usually be uncertain at the time the decision is made, and a firm's decision will depend partly on its attitude towards risk. Drawing on empirical results about business corruption, this paper describes the risks, uncertainties and benefits attached to bribery, and specifies their impact on firms' propensity to offer bribes. it then demonstrates how risk averse firms can be more inclined to offer bribes than risk neutral and risk attracted firms. (C) 2009 Elsevier Inc. All rights reserved.